Evaluation of Psychiatric Diagnosis, Demographic and Clinical Features in Adolescents With Suicide Attempts - Akın, Elif; Berkem, Meral (Fırat University, 2012)
Objective: In this study we aimed to asses psychiatric, demographic and clinical characteristics of adolescents between the ages of 12 and 18. Materials and Methods: For this study, 36 adolescent patients between the ages of 12 and 18 who refer or are referred to Child and Adolescent Psychiatry Clinic because of suicide attempt between June 2009 and May 2010 were included. Sociodemographic characteristics of the participants were measured with a detailed form, clinical assesment was made with the Kiddie Schedule for Affective Disorders and Schizophrenia Present and Life Time Version, Results: Seventy five percent of the adolescents with suicide attempt were girls. Most of the cases were between the ages of 15-16. The suicide attempts were made by overdose drug intake except two adolescent boys who attempted falling from high. Psychopathology was diagnosed in 77.8 % of the suicide attempters. The most frequent psychiatric disorders diagnosed were in order depression, attention deficit hyperactivity disorder and conduct disorder. Conclusion: Primary psychiatric diagnoses have a key role in etiology of suicidal behavior. It is thought that the treatment and close follow of adolescents with symptoms of depression is crucial in prevention of suicide attempts.

Amaç: Bu çalışmada intihar girişiminde bulunmuş 12-18 yaş aralığındaki ergenlerde psikiyatrik tanıların, demografik ve klinik özelliklerin değerlendirilmesi amaçlanmıştır. Gereç ve Yöntem: Çalışmaya Çocuk ve Ergen Psikiyatrisi polikliniğine Haziran 2009- Mayıs 2010 tarihleri arasında intihar girişimi nedeniyle acil olarak başvurmuş veya konsülte edilmiş 12-18 yaş arasındaki 36 hasta alınmıştır. Katılımcıların sosyodemografik özellikleri ayrıntılı bir formla, klinik değerlendirmeleri Okul Çağı Çocukları için Duygulanım Bozuklukları ve Şizofreni Görüşme Çizelgesi- Şimdi ve Yaşam Boyu Şekli ile değerlendirilmiştir. Bulgular: İntihar girişiminde bulunanların ¾'ünü ergen kızlar oluşturmaktaydı. Vakaların çoğunluğu 15-16 yaşlarda toplanmıştı. Yüksekten atlayarak intihar girişiminde bulunan iki erkek ergen dışında vakalarda girişim aşırı doz ilaç alımıyla gerçekleşmişti. İntihar girişiminde bulunan ergenlerin % 77.8'inde psikopatoloji saptandı. En sık görülen psikiyatrik bozukluklar sırasıyla depresyon, DEHB (Dikkat Eksikliği ve Hiperaktivite Bozukluğu) ve davranım bozukluğu idi. Sonuç: İntihar davranışının etyolojisinde arasında birincil psikiyatrik bozukluklar önemli bir yer tutmaktadır. İntihar davranışını önlemede özellikle depresif belirtileri olan ergenlerin yakın takip ve tedavi edilmelerinin gerektiği düşünülmektedir.
İntihar Girişiminde Bulunan Ergenlerde Psikiyatrik Tanıların, Demografik ve Klinik Özelliklerin Değerlendirilmesi